2014
DOI: 10.15376/biores.9.4.6938-6949
|View full text |Cite
|
Sign up to set email alerts
|

Small Gains in Wood Recovery Rate when Disobeying the Recommended Motor-Manual Tree Felling Procedures: Another Reason to Use the Proper Technical Prescriptions

Abstract: An efficient wood harvesting activity aims to fully recover wood as a measure to increase the profit, but safety prescriptions should be obeyed each time when harvesting operations are performed. A study was carried out in three forest compartments in order to determine whether the actual tree felling procedures match the recommended ones and, if not, to compare how the used practices may affect the wood recovery when felling trees using a conventional undercut. The study yielded significant statistical differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Skidding performance, on the other hand, is rather low due to reasons such as reduced accessibility conditions ) and a poor management of workplace time often resulting in great delays . Then, the motor-manual tree felling and processing may cause serious injuries, even fatalities (Borz et al 2014) while the workers are exposed to noise (Tunay & Melemez 2008), vibrations (Rottensteiner et al 2012) and they are required to take uncomfortable postures during their work (Corella et al 2015). On the other hand, the fully mechanized harvester-forwarder systems proved to be highly productive and less physically demanding (Inoue & Kobayashi 1996) but they are very sensitive to the operational layout.…”
Section: Introductionmentioning
confidence: 99%
“…Skidding performance, on the other hand, is rather low due to reasons such as reduced accessibility conditions ) and a poor management of workplace time often resulting in great delays . Then, the motor-manual tree felling and processing may cause serious injuries, even fatalities (Borz et al 2014) while the workers are exposed to noise (Tunay & Melemez 2008), vibrations (Rottensteiner et al 2012) and they are required to take uncomfortable postures during their work (Corella et al 2015). On the other hand, the fully mechanized harvester-forwarder systems proved to be highly productive and less physically demanding (Inoue & Kobayashi 1996) but they are very sensitive to the operational layout.…”
Section: Introductionmentioning
confidence: 99%
“…Laschi et al (2016) analyzed accident records and concluded that felling is definitely the most dangerous activity in forest operations. Even if there is a small loss of production due to rest breaks, the costs associated with accidents and the well-being of a safe work environment are factors that outweigh these losses, results also reported by Borz et al (2014), who compared the production gains in motor-manual felling by disregarding recommended safety procedures. The authors concluded that the productive and monetary gains are too low to be worth taking risks in a dangerous approach of the operation (Borz et al 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Even if there is a small loss of production due to rest breaks, the costs associated with accidents and the well-being of a safe work environment are factors that outweigh these losses, results also reported by Borz et al (2014), who compared the production gains in motor-manual felling by disregarding recommended safety procedures. The authors concluded that the productive and monetary gains are too low to be worth taking risks in a dangerous approach of the operation (Borz et al 2014). On the other hand, the results found by Montorselli et al (2010) seem to deny the common sense that safety practice is inversely proportional to productivity.…”
Section: Discussionmentioning
confidence: 76%
“…While the topic is still debated, further exploration is required to see if the postures adopted during the work are the sole factor causing MSDs. This is important especially in forest operations where the workers are exposed, in addition to job-related risks, to other harmful environmental and technology-related factors [14,37].…”
Section: Discussionmentioning
confidence: 99%